Research Status of Initiation and Expansion Behavior of Gear Fatigue Cracks - Yuan Jie; Ji Hongchao; Song Changzhe; Pei Weichi; Li Jingsheng (Jixie chuandong)
The comprehensive efficiency of the gear transmission directly restricts the development quality of transportation, construction, wind power and other fields, and the requirements of gear transmission power, load capacity and life expectancy improve gradually. However, the fatigue failure of gear greatly limits the performance and reliability of modern gear equipment. The present situation of fatigue crack initiation and propagation of gear is discussed comprehensively, and the main forms and causes of the gear failure are introduced. This research induces the factors affecting the fatigue strength of gears, summarizes three types of gear cracks, the crack initiation and extension method, and the existing gear fatigue crack simulation method. It is used to describe the microstructure mechanical behavior of gear fatigue, improve the understanding of the related characteristics and mechanism of gear fatigue, and study and analyze the remaining service life of gear fatigue tests. Finally, some suggestions on how to avoid gear cracks are put forward.